Study of knowledge, attitude, practice of rational use of medicines among interns at Mc Gann teaching district hospital, Shivamogga- a descriptive cross-sectional study - Hanumaiah, Vedavathi; Revankar, Shreenivas; P., Abhishek C. (International Journal of Basic & Clinical Pharmacology, 2021)
Background: Rational use of medicines requires that the patients receive medication appropriate to their clinical needs, in doses that meet their own individual requirements for an adequate period of lime, and at the lowest cost to them and to their community. Objective of the study were like descriptive cross- sectional study was conducted to determine and identify the level of knowledge, attitude and practice regarding rational use of medicines among the interns. Methods: A validated structured questionnaire containing 19 questions regarding rational use of medicines in knowledge, attitude and practice (KAP) format was distributed in hand among 109 interns affiliated to this institution. Descriptive statistics were used to illustrate the results in the form of number and percentage. Results: Out of 109 interns, 102 completed the questionnaire and were included in the final analysis. Majority of interns who participated in study were aware of the concept of rational use of medicine but the knowledge related to EML (essential medicines list), P drugs, schedule H drugs and number of FDCs (fixed dose combination) in EML was limited. Conclusions: As interns are future prescribers, they need to be aware of all the aspects of rational use of medicine and there is need to emphasise on learning module and training programs to ensure the interns have knowledge of rational use of medicines.